Syndesmotic Implant Removal: Does It Really Improve Ankle Dorsiflexion Range of Motion?. Issue 4 (16th October 2019) - Kwon, John Y.; Wusu, Timilien; Briceno, Jorge; Kaiser, Philip; Cronin, Patrick; Leblanc, Alyssa; Velasco, Brian; Miller, Christopher
Category: Ankle Introduction/Purpose: There is limited evidence that removal of syndesmotic implants is beneficial. Despite this, many surgeons advocate removal based on previous studies suggesting improved ankle dorsiflexion. Methodologic difficulties make the validity and applicability of previous works questionable. The purpose of this study was to examine the effect of ankle dorsiflexion after syndesmotic implant removal using radiographic measurements of ankle dorsiflexion before and after screw removal utilizing a standardized, applied load. Methods: All patients undergoing isolated syndesmotic implant removal were consented for participation. Ankle dorsiflexion was measured radiographically at three different time points: (I) immediately before implant removal intraoperatively, (II) immediately after implant removal intraoperatively and (III) approximately three months after implant removal. A standardized dorsiflexion torque force of 33.4 newton-meter (Nm) was applied to the ankle by a research assistant using a tensiometer at these time points and a perfect lateral radiograph of the ankle was obtained. Four reviewers independently measured ankle dorsiflexion on randomized, deidentified and blinded images using a digital measurement tool. Chi-square tests were used for categorical variables. Paired T-test or analysis of variance (ANOVA) with repeated measures was used for continuous variables. Intra-class correlation coefficients (ICC) were calculated using a 2-way random effects model and the absolute agreement definition. Results: 29 patients met inclusion criteria and were enrolled in the study. There were 11 men (38%) and 18 women (62%). The mean, and standard deviation, age was 50.3 ± 16.9 years (range 19-80). The mean ankle dorsiflexion pre-operatively, post-op and at 3 month follow up was 13.7°± 6.6°, 13.3°±7.3° and 11.8°±11.3°, respectively (p=0.466). For subsequent analysis, 5 patients were excluded due to potential cofounding effect of retained suture button devices. Analysis of the remaining 24 patients demonstrated similar results with no statistically significant difference in ankle dorsiflexion at all three time points. Conclusion: Removal of syndesmotic screws does not improve ankle dorsiflexion motion and should not be used as an indication for screw removal.